Espaços individuais para novilhos confinados - Cattelam, Jonatas (2012)
The objective, of this study, was evaluated, different individual spaces for steers feedlot finished in group pens and yours effects on patterns behavioral and performance. Forty eight steers, with average initial of twenty months and 243.4 kg, were used. Animals were feedlot, four for pen, allocated in treatments accorded the individual space, 2.5, 5.0 and 10 m2, with four pens for treatment. The animals were feedlot until reaching estimated cold carcass weight of 220 kg. The diet, with 115 g of crude protein and 705 g of total digestible nutrient by kg of diet in dry matter (DM), contained roughage: concentrate relation of 39:61 (DM basis). The complete randomized block experimental design was used. The dry matter intake, with intakes of 8.21; 8.29 and 8.41 kg, for steers with individual spaces of 2.5; 5.0 and 10 m2, respectively, as well the average daily gain was simulated between the different spaces, with means of 1.32; 1.41 and 1.47 kg, in the same order. The steers feed efficiency was not influenced by space allowance. The individual space not influenced the time spent to feeding, idle and rumination, which showed mean of 244.1; 790.3 and 405.6 minutes/day, respectively. Likewise, the number of times that animals showed each of the behaviours, as well the changes in posture during idle and rumination were similar between the different spaces evaluated. The total time that the animals remained standing or lying was not influenced by individual space, with average duration of 610.0 and 830.0 minutes/day, respectively, and the realization of activities in synchronism, not difference between the different spaces, the average time that the animals fed, standing or lay down in synchrony was 85.8, 308.0 and 468.4 minutes/ day, in the same order. The total number of disputes, with 21.9, 21.5 and 19.7 events between animals kept in spaces, 2.5, 5.0 and 10 m2, in the same order, and the number of non-agonistic interaction was not influenced by individual space available. Confined steers with 5.0 and 10 m2, extended their members 8.8 and 9.7 times per day, respectively, superior to animals maintained on individual spaces of 2.5 m2, this behavior made 4.3 times per day. The cleanliness differed between the spaces, with values of 3.2, 2.4 and 1.1 for steers with individual spaces of 2.5, 5.0 and 10 m2 respectively, as well as respiratory rate, with 27.1, 24.8 and 22.7 breaths / minute, in the same order. The hot and cold carcass weight, 226.0 and 222.0, respectively, and hot and cold carcass dressing, 58.5 and 57.0 kg/ 100 kg by live weight, in the same order, were not influenced by individual space. For all spaces evaluated, the carcass required minimum fat thickness, 3 mm. The weights and percentage of commercial cuts, also the weight and participation tissues in carcass were similar between different spaces. Color, texture, marbling, sensorial characteristics and shear force, were not influenced by individual space.